2017
DOI: 10.1177/0886260517742150
|View full text |Cite
|
Sign up to set email alerts
|

Abuse of Older Persons With Cognitive and Physical Impairments: Comparing Percentages Across Informants and Operational Definitions

Abstract: This study compared percentages of elder abuse reported by older adults and their family caregivers, using reports from attending medical professionals to triangulate the reports. Percentages were also compared using different criteria proposed in the literature. In total, 1,002 older Chinese aged 55 years or above and their primary family caregivers were recruited from three leading public hospitals in Guangdong, People's Republic of China. Caregivers and care recipients were separately interviewed and provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…It is unclear how to facilitate disclosure among older adults who lack capacity. Among patients with cognitive impairment, evidence suggests that caregivers are willing to disclose EA (Fang & Yan, 2017;Ho, Wong, Chiu, & Ho, 2017) and, thus, disclosure techniques targeted toward caregivers may need to be developed. Alternatively, disclosure techniques that facilitate disclosure among older adults who lack capacity may be possible given evidence that older adults with mild to moderative cognitive impairments are able to recall and describe abusive events (Wiglesworth et al, 2009).…”
Section: Future Directionsmentioning
confidence: 99%
“…It is unclear how to facilitate disclosure among older adults who lack capacity. Among patients with cognitive impairment, evidence suggests that caregivers are willing to disclose EA (Fang & Yan, 2017;Ho, Wong, Chiu, & Ho, 2017) and, thus, disclosure techniques targeted toward caregivers may need to be developed. Alternatively, disclosure techniques that facilitate disclosure among older adults who lack capacity may be possible given evidence that older adults with mild to moderative cognitive impairments are able to recall and describe abusive events (Wiglesworth et al, 2009).…”
Section: Future Directionsmentioning
confidence: 99%
“…For instance, homeless adults suffer from a high prevalence of functional and cognitive impairments at earlier ages than the general population (Brown et al, 2017). We hypothesize that these may limit capacity to recognize danger and to self-defend (Fang & Yan, 2021;Poole & Rietschlin, 2012;Williams, Racette, Hernandez-Tejada, & Acierno, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…We found 119 studies that reported data from 68 AOP measurement instruments eligible for inclusion. Three studies reported on two instruments (Badenes-Ribera et al, 2021;Buri Hilary et al, 2009;Conrad et al, 2009) and one reported on three instruments (Fang & Yan, 2021). The included studies were published between 1986 and 2023.…”
Section: Results Of the Searchmentioning
confidence: 99%